2019
DOI: 10.1029/2019jc015413
|View full text |Cite
|
Sign up to set email alerts
|

Kuroshio Shape Composition and Distribution of Filamentous Diazotrophs in the East China Sea and Southern Yellow Sea

Abstract: The filamentous Trichodesmium and Richelia/Calothrix appear to be crucial N 2 -fixing cyanobacteria throughout the warm oligotrophic ocean, particularly in western boundary currents. The Kuroshio, the hotspot of N 2 fixation in the Pacific Ocean, intrudes into the East China Sea (ECS) and southern Yellow Sea (SYS), which may profoundly influence composition and distribution of filamentous diazotrophs. We provide high spatial resolution dataset of filamentous diazotrophs in the ECS and SYS in July and August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 80 publications
(252 reference statements)
1
21
1
Order By: Relevance
“…Specifically, we observed that nutrient concentrations and structure play important roles in regulating phytoplankton biomass, especially for diatoms and dinoflagellates, as revealed by the significant positive correlations between PB (and brassicasterol and dinosterol) and DIN (and DIN/DIP and DIN/Si) (Figure 4). This result is consistent with previous findings in the CRE, the ECS and the southern YS in summer (Jiang et al, 2015;Wu et al, 2016), because sufficient nutrients from the Changjiang River induce high phytoplankton biomass in these areas, and the runoff of the Changjiang River is much higher in summer, with the large influencing area of the CDW and forming the fronts beyond 125 • E and 33 • N (Figure 3E; Wei et al, 2015;Jiang et al, 2019b). In contrast, C 37 alkenones showed significant negative correlations with nutrients and temperature, but positive ones with salinity and depth (Figure 4).…”
Section: Spatial Distribution Of Marine Lipid Biomarkerssupporting
confidence: 93%
“…Specifically, we observed that nutrient concentrations and structure play important roles in regulating phytoplankton biomass, especially for diatoms and dinoflagellates, as revealed by the significant positive correlations between PB (and brassicasterol and dinosterol) and DIN (and DIN/DIP and DIN/Si) (Figure 4). This result is consistent with previous findings in the CRE, the ECS and the southern YS in summer (Jiang et al, 2015;Wu et al, 2016), because sufficient nutrients from the Changjiang River induce high phytoplankton biomass in these areas, and the runoff of the Changjiang River is much higher in summer, with the large influencing area of the CDW and forming the fronts beyond 125 • E and 33 • N (Figure 3E; Wei et al, 2015;Jiang et al, 2019b). In contrast, C 37 alkenones showed significant negative correlations with nutrients and temperature, but positive ones with salinity and depth (Figure 4).…”
Section: Spatial Distribution Of Marine Lipid Biomarkerssupporting
confidence: 93%
“…Our result revealed slightly higher NFR on the surface than at the 10% light depth (∼5–45 m with 100–250 μmol quanta m −2 s −1 ). This result was highly supported by the abundant filamentous diazotrophs in upper 45 m (Jiang et al., 2019) as well as their high adaptability to this relatively low light environment (Lu et al., 2018; Villareal, 1990). Previous studies also showed relatively low variability in NFRs throughout the euphotic zone, except for 1% of the surface irradiance, such as the ECS (Zhang et al., 2012) and Northwestern Atlantic Ocean (Capone et al., 2005).…”
Section: Discussionmentioning
confidence: 89%
“…Because they are close to the mainland, high terrestrial inputs of P and Fe are observed therein compared with the open ocean (Jickells et al., 2005; Martiny et al., 2019), probably resulting in an alleviation of P and Fe limitation of diazotrophs (Shiozaki et al., 2014). Particularly diazotrophic cyanobacteria Trichodesmium (Capone et al., 1997), frequently occurs and occasionally blooms in western boundary currents, including the Gulf Stream (Palter et al., 2020), Brazil Current (Detoni et al., 2016), East Australian Current (Armbrecht et al., 2015), and Kuroshio (Jiang et al., 2019; Jiang, Li, et al., 2018; Shiozaki, Takeda, et al., 2015). Western boundary currents seem to be hotspots of marine N 2 fixation (Shiozaki et al., 2010; Tang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some Calothrix phylotypes were positively correlated with both salinity and HM, as well as low N ( Supplementary Figure S5B1 ). Jiang et al (2019) also noted positive correlations between Calothrix and these soil properties, and suggested that these cyanobacteria likely play an important role in suppling N in habitats with low N fertility. Others have also noted that Sphingomonas spp.…”
Section: Discussionmentioning
confidence: 87%